2019
DOI: 10.1002/psp.2243
|View full text |Cite
|
Sign up to set email alerts
|

Left‐behind villages, left‐behind children: Migration and the cognitive achievement of rural children in China

Abstract: Although the potential effects of migration on the cognitive development of children in origin communities reflect both household‐ and community‐level processes, few studies have examined how community‐level migration affects child cognitive development. By applying multilevel methods to nationally representative data of 2,248 children from 427 villages in China, we examine whether village migration intensity influences child cognitive ability and if so, what accounts for this influence. The findings suggest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…However, its impacts on children's development are mixed. Left-behind children without parents' supervision are at greater risk of child victimization and accidental injury (Chen, Sun, et al, 2020b), and they are also more likely to encounter cognitive and behavioral problems (Lu et al, 2019;Xie et al, 2019). Those risks and negative impacts may vary according to different parental migration types and particular stages of children's growth (Liang, 2016;Lu, 2012).…”
Section: How Are Educational Expectations Of Left-behind Children Determined? Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its impacts on children's development are mixed. Left-behind children without parents' supervision are at greater risk of child victimization and accidental injury (Chen, Sun, et al, 2020b), and they are also more likely to encounter cognitive and behavioral problems (Lu et al, 2019;Xie et al, 2019). Those risks and negative impacts may vary according to different parental migration types and particular stages of children's growth (Liang, 2016;Lu, 2012).…”
Section: How Are Educational Expectations Of Left-behind Children Determined? Review and Hypothesesmentioning
confidence: 99%
“…A large body of literature has revealed that left-behind children are at greater risk of child victimization, accidental injury and a range of psychological problems (Chen, Sun, et al, 2020b). Without parental care, left-behind children frequently experience cognitive and behavioral problems (Lu et al, 2019;Xie et al, 2019). With the absence of parental guardianship, many left-behind children receive little academic support and supervision at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the large body of literature, it has been found that left-behind children are more prone to child injury [12,13], accidental injury, and psychological disorders [14,15]. In the absence of parental care, left-behind children are more likely to exhibit cognitive and behavioral difficulties [16][17][18]. Children's physical and mental health can be negatively impacted by parent-child separation due to a lack of love, care, and parental supervision [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%